KINETIC DETERMINATION OF GOLD(III) BASED ON ITS INHIBITORY EFFECT IN OXIDIZING HOMOGENOUS REACTION SYSTEM - Micić, Ružica; Mitić, Snežana; Simonović, Ranko; Sejmanović, Dragana (Bulletin of Natural Sciences Research, 2016)
Development and application of a simple, fast, green analytical kinetic method for the determination of micro-amounts of gold(III ) ions, were presented in this paper. The method was based on the inhibitory effect of traces of Au(III) ions on the redox reaction between disodium-6-hydroxy-5-[(4-sulfophenyl)azo]-2-naphtalenesulfonate (artificial azo-dye "Sunset Yellow FCF", E110 in further text selected as SY ) and hydrogen-peroxide, in alkaline media of borate buffer. All experimental parameters affecting to the determination: reagent concentrations, pH and temperature were investigated and optimised. Working experimental conditions are set according to the highest sensitivity of the proposed kinetic method for the determination of Au(III) ions. The linearity of the method was obtained within the range 1.97-59.07 μg/mL of Au(III) ions with relative standard deviation of 3.66- 0.43 %, respectively. The influence by possible interference effects by major ions on the determination of Au(III) and their limits are investigated, at the constant Au(III) concentration of 39.39 μg/mL. The results of Au(III) determination in samples obtained by proposed kinetic method and comparative ICP-OES method were statistically agreeable. Obtained results for Au(III) determination in analyzed samples, as well as the development and validation of the proposed analytical procedure have given and discussed.